Efficiency of the Position Tracking Photovoltaics using Microcontroller Atmega - Anggara Trisna Nugraha; Moch Fadhil Ramadhan; Muhammad Jafar Shiddiq (Merdeka Malang University, 2022)
So far, solar cells are known to have many weaknesses in terms of installation and position to the sun, so that the performance of solar cells on rechargeable batteries is less than optimal. Therefore, additional tools are needed to support these solar cells so that they can work optimally and produce bigger currents. Compare a sunlight tracker with an LDR system, and compare a sunlight tracker with a direct sunlight sensor with a passive system. Atmega16 is used as a control motor and automatic charger, LDR is used as a sunshine receiver, and a DC motor and a stepper are used as a sunshine indicator player. The solar cell used has a capacity of 20 WP. The automatic filling system uses a microcontroller to increase the cost and efficiency of installation. After that, the two systems will be compared first to find out the difference in power generated by the solar cell system using a tracer and a passive tracer. Using a tracking system will collect data for a week, while using a passive system will collect data for a week. By using the result data to be analyzed, the system can be analyzed and compared, and its efficiency can be determined. The solar cell tracking system is expected to increase battery charge faster than passive locations